Pengaruh Dosis Fosfor Dan Urin Sapi Terhadap Perkembangan Penyakit BBV (Busuk Batang Vanili) Dan Pertumbuhan Tanaman Vanili (Vanilla planifolia) - Haryuni Haryuni; Teguh Supriyadi; Tyas Soemarah Kurnia Dewi; Endang Suprapti; Achmadi Priyatmojo; Alfiansyah Al Afghani Erping Sitompul (JURNAL ILMIAH AGRINECA, 2018)
This research aims to know the influence of dosing cow urine phosphorus and against foul disease progression stems vanilla (BBV) and growth of vanilla (Vanilla planifolia). The research method used a basic design with factorial Randomized Complete Design (RAL) consisted of two treatment factors 3 deuteronomy that is a dose of 6 g/phosphorus plant; a dose of phosphorus 9 g/plant; a dose of phosphorus 12 g/plant (named as P1; P2; P3). Cow urine dose treatment consists of 4 levels, namely without the cow urine dose treatment; cow urine dose 10 ml/plant; cow urine dose 20 ml/plant; cow urine dose 30 ml/plant (named as U1; U2; U3; and U4). There are 12 treatment combinations, each combination treatment is repeated as many as 3 times until there are 36 combinations of treatment. The results of this study show that treatment doses of phosphorus had no effect against the real parameters of intensity of attacks, number of leaves, plant height, the weight of the fresh root, root volume, and weight of the dried root but real effect against the length of the roots and the weight of the dry stover. Cow urine dose treatment very real effect against the intensity of the attacks, the weight of the dry stover and dried root weight but has no effect against a real high parameters of plants, number of leaves, fresh root weight, root volume, length of the root. The combination of the treatment effect is evident against the fresh root weight parameters and the weight of the dry stover but do not affect the real intensity of the attack against Fusarium oxysporum f. sp. vanillae cause foul stem of vanilla (BBV), plant height, the number of leaves, fresh stover, heavy volume root, root length, and weight of the dried root. The highest dry weight stover is shown by the P2U2 treatment of 7.5 g as well as the lowest indicated by P1U0 treatment of 3.1 g. Best treatment on the intensity of the attacks of Fusarium oxysporum f.sp. vanillae indicated by P1U0 of 16,67%.